Synthesis of β-carboline fatty alcohol hybrid molecules and characterization of their biological and antioxidant activities - Kontham V.; Ippakayala B.; Madhu D. (My University, 2025)
Nine new β-carboline fatty alcohol hybrids were synthesized from natural amino acid L-tryptophan by the conjugation of 10-undecen-1-ol via ester linkage. All the synthesized products were characterized in each step by spectral techniques (1H, 13C NMR mass and HRMS). Synthesized β-carboline derivatives (7a-i) were screened for biological activities such as antimicrobial, antifungal, anti-biofilm and anticancer. Compounds 7d and 7f showed most potent antimicrobial activity against Bacillus subtilis MTCC 121, Micrococcus luteus MTCC 2470, Staphylococcus aureus MTCC 96 and Candida albicans MTCC 3017 microbial strains ranged from 2.8 to 28.3 µg/mL. Biofilm inhibition assay showed that the compound 7f exhibited better activity against three bacterial stains with IC50 values from 1.8 to 2.9 µM. All the β-carboline derivatives showed cytotoxic activity, among them compounds 7f and 7h (IC50 values 9.1 and 11.4 µM) were exhibited potential activity. Free radical scavenging activity via DPPH assay revealed that compound 7g acted as a good antioxidant molecule than all the tested compounds. © 2021